Tactile and Somatic Hallucinations in a Muslim Population of Psychotic Patients - Lim, Anastasia; Blom, Jan Dirk (Frontiers in Psychiatry, 2021)
Background: Tactile and somatic hallucinations are distressing phenomena that have hardly been researched. The few studies that have been published focus on their occurrence in neurodegenerative disorders and substance use, and, surprisingly, not on schizophrenia spectrum disorders. Objective: To fill this gap in our knowledge, we sought to explore the phenomenological characteristics of tactile and somatic hallucinations in a group of psychotic Muslim patients. Since many Muslims attribute such experiences to jinn (invisible spirits) and jinn are often perceived in multiple sensory modalities, we not only charted the involvement of the tactile and somatic modalities but also their interrelatedness with hallucinations in other sensory modalities. Methods: We performed a cross-sectional study using a semi-structured interview and dedicated questionnaire. Results: Of the 42 Muslim inpatients mostly diagnosed with a schizophrenia spectrum disorder, 62% reported to suffer from tactile and/or somatic hallucinations. Their phenomenological characteristics varied, with 96% being multimodal in nature and 38% taking the form of full-blown entity/jinn encounters. In comparison to other entity experiences, the involvement of the tactile and somatic modalities was exceptionally high, as was the level of ensuing distress. Regarding the order of recruitment of the various sensory modalities, we suggest the involvement of an underlying stochastic process. Conclusion: Muslim patients with severe psychosis can have tactile and somatic hallucinations, of which a large number are multimodal or full-blown entity/jinn encounters, which are almost invariably appreciated as harrowing. On the basis of our findings we make recommendations for further research and clinical practice.